Peran TPQ dalam Meningkatkan Kualitas Kemampuan Baca dan Tulis Alqur'an pada Anak di TPQ Kecamatan Muara Bangkahulu Kota Bengkulu - Agung Syahru Ramadhan; Hery Noer Aly; Ahmad Suradi (Journal on Education, 2023)
this research are: 1), What is the role of TPQ in Improving the Quality of Reading and Writing Ability of the Qur'an in Children in Muara Bangkahulu District, Bengkulu City?, 2), What are the Supporting Factors faced by TPQ in an effort to Improve the Quality of Ability to Read and Write Alqur 'an on Children in Muara Bangkahulu District, Bengkulu city? 3) What are the inhibiting factors faced by TPQ in an effort to improve the quality of the ability to read and write the Koran in children in the Muara Bangkahulu sub-district, Bengkulu city? The results of the study refer to the main processes in the TPQ namely facilitating complete learning of the All-Qur'an, controlling and monitoring periodically the development of All-Qur'an education, carrying out overall overall development and continuity to certain units. Malkal based on the results of the TPQ research in the Balengalhulu Mualral Subdistrict, Kotal Bengkulu, has fulfilled these requirements. Supporting and inhibiting factors that arise in the learning process at TPQ come from three aspects, namely from the child, the child's parents, and the teacher/educator at TPQ.